Peningkatan Hasil Belajar Keliling Luas Bangun Datar Menggunakan Model PBL di Kelas IV SD - Ramadhayani Ramadhayani; Nelly Astimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research based on the low learning outcomes of students in mobile learning and the area of flat building because learning is still teacher centered so that the teacher does not provide opportunities for students to solve problems both individually and in groups thingking skills in solve the problem.The purpose of research to describe the improvement mobileand the area of flat building  learning outcomes with Problem-Based Learning model in class IV SDN 36 Cengkeh Padang City. This research is a classroom action research using qualitative and quantitative approach. The subjects were teachers and 28 students. The result of planning observation in cycle I is 76,78% and it increase to be 96,42%. in cycle II. The result of teacher aspect observation in cycle I is 78,57%  and it increase to be 98,21%in cycle II. The result of student aspect observation in cycle I is 75%  and it increase to be 98,21%in cycle II. The learning outcomes in cycle I is 60,89 and it increase to be 83,03 in cycle II.Keywords:Learning outcomes,Problem-Based Learning model Problem Based